CAPABILITY OF PUBLIC ORGANIZATIONSTRUCTURE AFTER REGIONAL EXTENTION IN WAY KANAN REGENCY (A Study on Basic Service Organization) - Yadi Lustiadi (International Conference On Law, Business and Governance (ICon-LBG), 2016)
A primary issue in this study is that Way Kanan, a 13-year-old district, since it was formed from the expansion of the North Lampung Regency, is not strong enough to show the ability to carry out effective public services, even it is still categorized as a remote area.The public organization structure of Way Kanandistrict that is essential element of organizational capability, has not effectively supported the management of existing resources towards the achievement of the main objectives of regional division that is the welfare of society.Research question is: how does the capability of public organizations basic service providers in Way Kanan district can effectively support the implementation of the main tasks of the organization? This study used a qualitative approach, through direct observation, in-depth interview and documentation. To test the validity of the data, triangulation techniquesare used. The results showed that there elements of the capabilities of the organizational structure generally are less effective to support the implementation of the main tasks of the departments, especially the elements of the chain of command, centralization, formalization and span of control, while other elements: the work specialization and departmentalization, can be considered quite effective.